Cytotoxic Potential of Essential Oil Isolated from Clibadium Surinamese L Leaves Against T47D Breast and HeLa Cervical Cancer Cells - Ulia, Rahmi Vika; suryati, Suryati; Santoni, Adlis (Molekul, 2023)
Semambu (C. surinamense L) plant is a shrub plant that is easy to find. Several terpenoid compounds have been isolated from this plant, previous studies have shown cytotoxic activity of terpenoid class compounds. Terpenoid compounds in a plant are mostly found in essential oils (monoterpenes and sesquiterpenes). So far, there has been no report on the cytotoxic potential of essential oils from the leaves of this plant. It is necessary to isolate the essential oils from C. surinamense L leaves and test their cytotoxic potential. Isolation of essential oil of C. surinamense L leaves was carried out by hydrodistillation method, the oil was obtained in the form of a light yellow liquid with a specific gravity of 0.968 g/mL. Analysis of chemical components with Gas Chromatography-Mass-Spectrometry (GC-MS) through comparison of data from the National Institute of Standards and Technologies (NIST) found that there were 55 compounds (monoterpene and sesquiterpene groups) with six main compounds, namely β-caryophyllene (30.4%), β-sesquiphellandrene (8.46%), 3 carene (8.16%), α-bisabolene (4.05%), α-humulene (4.0%), and epi- bicyclosesquiphellandrene (4.0%). The potential cytotoxic test of essential oil from isolation showed highly cytotoxic activity with the Brine Shrimp Lethality Test (BSLT) method against Artemia salina L shrimp larvae with LC50 value of 0.9261 μg/mL and Microculture tetrazolium test (MTT) method against T47D breast cancer cells and HeLa cervix with IC50 values of 12.72 μg/mL and 30.14 μg/mL.